2, 3, 7, 8‐tetrachlorodibenzo‐p‐dioxin exposure influence the expression of glutamate transporter GLT‐1 in C6 glioma cells via the Ca2+/protein kinase C pathway. Issue 11 (14th March 2016) - Zhao, Jianya; Zhang, Yan; Zhao, Jianmei; Wang, Cheng; Mao, Jiamin; Li, Ting; Wang, Xiaoke; Nie, Xiaoke; Jiang, Shengyang; Wu, Qiyun
Abstract: The widespread environmental contaminant, 2, 3, 7, 8‐tetrachlorodibenzo‐ p ‐dioxin (TCDD), is considered one of the most toxic dioxin‐like compounds. Although epidemiological studies have shown that TCDD exposure is linked to some neurological and neurophysiological disorders, the underlying mechanism of TCDD‐mediated neurotoxicity has remained unclear. Astrocytes are the most abundant cells in the nervous systems, and are recognized as the important mediators of normal brain functions as well as neurological, neurodevelopmental and neurodegenerative brain diseases. In this study, we investigated the role of TCDD in regulating the expression of glutamate transporter GLT‐1 in astrocytes. TCDD, at concentrations of 0.1–100 nm, had no significantly harmful effect on the viability of C6 glioma cells. However, the expression of GLT‐1 in C6 glioma cells was downregulated in a dose‐ and time‐dependent manner. TCDD also caused activation of protein kinase C (PKC), as TCDD induced translocation of the PKC from the cytoplasm or perinuclear to the membrane. The translocation of PKC was inhibited by one Ca 2+ blocker, nifedipine, suggesting that the effects are triggered by the initial elevated intracellular concentration of free Ca 2+ . Finally, we showed that inhibition of the PKC activity reverses the TCDD‐triggered reduction of GLT‐1. In summary, our results suggested that TCDD exposure could downregulate the expression of GLT‐1 in C6 via Ca 2+ /PKC pathway. The downregulation of GLT‐1 might participate in TCDD‐mediated neurotoxicity. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this study, we investigated the role of TCDD in regulating the expression of glutamate transporter GLT‐1 in astrocytes. TCDD, at concentrations of 0.1–100 nM, had no significantly harmful effect on the viability of C6 glioma cells. However, the expression of GLT‐1 in C6 glioma cells was downregulated in a dose‐and time‐dependent manner. TCDD also caused activation of protein kinase C (PKC), as TCDD induced translocation of the PKC from the cytoplasmor perinuclear to the membrane.